INDONESIA – CHINA BILATERAL COOPERATIONS: IMPACT OF CSP (COMPREHENSIVE STRATEGIC PARTNERSHIP) TOWARD INFRASTRUCTURE DEVELOPMENT UNDER JOKO WIDODO'S ERA - Arif Rahman Majid, Mohammad Latief Majid (UNIDA GONTOR, 2019)
Abstract This research is the answer to how strategic partnerships affect infrastructure development. The researcher focuses on the comprehensive strategic partnership between Indonesia-China toward Indonesia's infrastructure development under Joko Widodo's era. Furthermore, the author will explain the benefits of the collaboration for China as Indonesia's partner country. In addition, the researcher will elaborate by using variables which are delivered in bilateral concepts, and also will use qualitative methods, in which data collections are from the study of literature - books, journals, documents that are taken from websites and trusted websites to strengthen researcher's argument. The results of this study indicate that the impacts of comprehensive strategic partnership on Indonesia's infrastructure development are realizing Indonesia's national connectivity agenda which was listed in the MP3EI document with China's helping through investment. in addition, by helping Indonesia in developing infrastructure, China succeeded in realizing and expanding the 21st century silk road agenda. Keyword : Bilateral Relations; Comprehensive strategic Partnership; Infrastructure development.